HLA-DR phenotypes in Spanish coeliac children: their contribution to the understanding of the genetics of the disease. Issue 6 (June 1983) - Mearin, M L; Biemond, I; Peña, A S; Polanco, I; Vazquez, C; Schreuder, G T; de Vries, R R; van Rood, J J
Abstract : The DR-locus controlled B-cell antigens were studied in 163 unrelated Spanish coeliac children and 68 families of this group, nine of them with more than one coeliac patient, to obtain more information about the association between these antigens and coeliac disease. The results show that the most common coeliac phenotypes are DR3/DR7, DR7/DR5, DR3/other DR, and DR3/DR3. The family study confirmed the segregation of the disease with the above mentioned phenotypes. In eight of the nine multiple case families, all coeliac children shared both HLA-DR antigens. These findings make it unlikely that a single dominant gene linked to HLA-DR controls the susceptibility to coeliac disease. The phenotypes in the patients were not distributed according to the Hardy-Weinberg equilibrium. Thus, a model based on one recessive susceptibility gene linked to HLA-DR is not probable either. The complexity of the genetics of coeliac disease and some of the features shared with the HLA-DR pattern in juvenile insulin-dependent diabetes are discussed.